Regioselective O-acylation of myo-inositol 1,3,5-orthoesters: dependence of regioselectivity on the stoichiometry of the base - Sureshan, Kana M.; Devaraj, Subramanian; Shashidhar, Mysore S. (Tetrahedron, 2009)
A metal mediated unusual 1-3 acyl migration from C4-O to C2-OH of myo-inositol 1,3,5-orthoformate was observed during the alkylation of racemic 4-O-benzoyl-myo-inositol 1,3,5-orthoformate. This has been exploited for the selective esterification of either the C4(6)-OH or the C2-OH of myo-inositol by varying the amount of the base used. While the use of 1 equiv of the base (sodium hydride or potassium tert-butoxide) for the acylation of myo-inositol orthoesters gives the corresponding C4-ester exclusively, the use of two or more equivalents of base for the same reaction gives the C2-ester exclusively. The relatively higher stability of the alkoxide of racemic 2-O-acyl-myo-inositol 1,3,5-orthoester as compared to the alkoxide of 4-O-acyl-myo-inositol 1,3,5-orthoester is suggested to be responsible for the observed isomerization. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Acylation; Cyclitol; Inositol; Orthoester; Regioselectivity; transesterification

Strength from weakness: the role of CH center dot center dot center dot N hydrogen bond in the formation of wave-like topology in crystals of aza-heterocycles - Shivakumar, Kota; Vidyasagar, Adiyala; Naidu, Andra; Gonnade, Rajesh G.; Sureshan, Kana M. (Crystengcomm, 2012)
Crystal engineering has succeeded in the design and construction of various architectures such as tapes, ribbons, rosettes, layers etc. Though wavy layer packing is known to occur in crystals, no crystal engineering attempts have been ventured to create wavy layer topology in crystals. Aromatic nitrogen heterocyclics (ANHs) are known to preferentially self assemble in lateral fashion through edge-to-edge CH center dot center dot center dot N hydrogen bonds. Exploiting this preferential lateral assembly of ANHs, we have engineered wavy layer architectures in the crystals of various substituted quinolines.

Topochemical click reaction: spontaneous self-stitching of a monosaccharide to linear oligomers through lattice-controlled azide-alkyne cycloaddition - Pathigoolla, Atchutarao; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2012)
Keywords: Click chemistry; green chemistry; polymerization; pseudosugars; topochemistry

Weak becomes strong: remarkable strength of C-H center dot center dot center dot pi hydrogen bond in the presence of O-H center dot center dot center dot O hydrogen bonds in the crystal stabilization - Sureshan, Kana M.; Gonnade, Rajesh G. (CrystEngComm, 2013)
We report crystallographic evidence for the significance of C-H center dot center dot center dot pi hydrogen bonds in the crystal stabilization of 1,4-di-O-benzoyl-myo-inositol. The strength of this otherwise weak hydrogen bond matches with the strength of O-H center dot center dot center dot O hydrogen bonds.

Crystal-to-crystal synthesis of helically ordered polymers of trehalose by topochemical polymerization - Hema, Kuntrapakam; Gonnade, Rajesh G.; Sureshan, Kana M. (Angewandte Chemie-International Edition, 2020)
The synthesis of crystalline helical polymers of trehalose via topochemical azide-alkyne cycloaddition (TAAC) of a trehalose-based monomer is presented. An unsymmetrical trehalose derivative having azide and alkyne crystallizes in two different forms having almost similar packing. Upon heating, both the crystals undergo TAAC reaction to form crystalline polymers. Powder X-ray diffraction (PXRD) studies revealed that the monomers in both the crystals polymerize in a crystal-to-crystal fashion; circular dichroism (CD) studies of the product crystals revealed that the formed polymer is helically ordered. This solvent-free, catalyst-free polymerization method that eliminates the tedious purification of the polymeric product exemplifies the advantage of topochemical polymerization reaction over traditional solution-phase polymerization.
Keywords: Click reaction; helical polymers; polysaccharide; topochemical reactions; trehalose